The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.908363
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Neuropsychiatric Features of COVID-19 Patients After Hospital Dismission: An Italian Sample

Abstract: Background and AimsRecent studies suggest cognitive, emotional, and behavioral impairments occur in patients after SARS-CoV-2 infection. However, studies are limited to case reports or case series and, to our knowledge, few of them have control groups. This study aims to assess the prevalence of neuropsychological and neuropsychiatric impairment in patients after hospitalization.MethodsWe enrolled 29 COVID+ patients (M/F: 17/12; age 58.41 ± 10.00 years; education 11.07 ± 3.77 years, 2 left handers) who needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As reported in Table 2 , the negative effects of COVID-19 infection on cognitive performance in healthy people were identified in 39 out of 46 studies (85%). Five out of seven studies performed in the short period (1–4 months) found a general worsening in cognitive performance [ 53 , 54 , 57 , 58 ], specifically, in verbal memory [ 54 , 57 ] and attention tasks [ 55 ]. On the contrary, Johnsen et al [ 56 ] and Priftis at al.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in Table 2 , the negative effects of COVID-19 infection on cognitive performance in healthy people were identified in 39 out of 46 studies (85%). Five out of seven studies performed in the short period (1–4 months) found a general worsening in cognitive performance [ 53 , 54 , 57 , 58 ], specifically, in verbal memory [ 54 , 57 ] and attention tasks [ 55 ]. On the contrary, Johnsen et al [ 56 ] and Priftis at al.…”
Section: Resultsmentioning
confidence: 99%
“…Episodic memory has already been tested in COVID patients using the AVLT test, as we did, early after the acute infection, with evidence of memory impairment, especially in free and delayed verbal recall and recognition. However, in this study, the primacy/recency effect and episodic memory performances long after the acute infection have not been tested [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Perrottelli et al’s systematic review [ 48 ] indicated widespread neurocognitive impairment across a large majority of studies [ 5 , 36 , 42 , 43 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], although several studies found no significant impairment in COVID-19 patients [ 37 , 45 , 75 , 76 , 77 , 78 , 79 ]. While most assessments used screening tests, providing valuable insights into COVID-19-related neurocognitive impairment, only a few studies employed a comprehensive neuropsychological battery.…”
Section: Introductionmentioning
confidence: 99%